Photosynthetic acclimation in trees to rising atmospheric CO2: a broader perspective (Photosynthesis Research, 1994)
Analysis of leaf-level photosynthetic responses of 39 tree species grown in elevated concentrations of atmospheric CO 2 indicated an average photosynthetic enhancement of 44% when measured at the growth [CO2]. When photosynthesis was measured at a common ambient [CO2], photosynthesis of plants grown at elevated [CO2] was reduced, on average, 21% relative to ambient-grown trees, but variability was high. The evidence linking photosynthetic acclimation in trees with changes at the biochemical level is examined, along with anatomical and morphological changes in trees that impact leaf- and canopy-level photosynthetic response to CO 2 enrichment. Nutrient limitations and variations in sink strength appear to influence photosynthetic acclimation, but the evidence in trees for one predominant factor controlling acclimation is lacking. Regardless of the mechanisms that underlie photosynthetic acclimation, it is doubtful that this response will be complete. A new focus on adjustments to rising [COz] at canopy, stand, and forest scales is needed to predict ecosystem response to a changing environment.